Acantholytic pityriasis rubra pilaris associated with topical use of imiquimod 5%: case report and literature review, - Oriete Gerin Leite; Sandra Tagliolatto; Elemir Macedo de Souza; Maria Letícia Cintra (Sociedade Brasileira de Dermatologia, 2020)
Abstract Topical use of immune response modifiers, such as imiquimod, has increased in dermatology. Although its topical use is well tolerated, it may be associated with exacerbations of generalized cutaneous inflammatory diseases, possibly through the systemic circulation of pro-inflammatory cytokines. This report describes a case of development of pityriasis rubra pilaris, a rare erythematous-papulosquamous dermatosis, in a woman aged 60 years during treatment with imiquimod 5% cream for actinic keratosis. It evolved with erythrodermic conditions and palmoplantar keratoderma, presenting progressive clinical resolution after the introduction of methotrexate. The authors emphasize the importance of recognizing possible systemic reactions associated with the topical use of imiquimod.